Peran Yayasan Pendidikan Islam dan Asuhan Yatim/Miskin Al-Mukmin Ngruki dalam Mengatasi Radikalisme dan Menanamkan Moderasi Beragama - Rahmawati, Lady Eka (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2024)
This article aims to explain the role of the Islamic Education and Orphan/Poor Al-Mukmin Foundation (YPIA) in improving Islamic religious education, overcoming radicalism, and instilling religious moderation in students in Ngruki, Cemani, Sukoharjo, Central Java. This research is library research with a qualitative approach in the form of field research. Data collection techniques are carried out by observation, interviews and documentation of all reference sources. The results of this research conclude that the Islamic Education Al-Mukmin Ngruki Foundation plays an active role in educating the nation's next generation and applies a moderate attitude to all business charity units under its auspices. YPIA educational institutions consist of PAUD IT Al-Mukmin, RA Al-Amin II, RA Al-Amin III, SD Al-Amin, SMA 1 Islam Gading Surakarta, Islamic High School al-Mukmin (STIM) Surakarta and Pondok Pesantren Al-Mukmin Ngruki Surakarta. In the social and economic fields, YPIA oversees the Orphan/Poor Orphanage Institution, the Zakat Collection Unit (UPZ) or Baitul Mal Al-Mukmin (BMA), and the Ta'awun Islamic Boarding School Cooperative. The diversity of YPIA's charity business units reflects the moderation of diversity in overcoming the development of radicalism from an early age.